Effectiveness of Durian Peel Extract as A Natural Anti-Bacterial Agent - Arlofa, Nina; Ismiyati, Ismiyati; Kosasih, Muhammad; Fitriyah, Nurul H. (Jurnal Rekayasa Kimia & Lingkungan, 2019)
Durian (durio zibertinus) is a native tropical fruit from Southeast Asia, especially Indonesia. Durian peel is the highest composition of durian fruit (60-75%), and is still considered as waste that causes environmental problems. This study aimed to analyze the content of secondary metabolites extract, to analyze the anti-bacterial activity of durian peel extract against gram-negative and gram-positive bacteria, and to calculate the effectiveness of durian skin durian peel extract as a natural anti-bacterial ingredient in hand sanitizer products by using the paper disc method. Durian peel was extracted with ethanol to obtain extract solution which was then separated from the solvent and applied as an ingredient for hand sanitizer. The Analysis results showed that durian peel extract contains triterpenoids, alkaloids, and saponins, which are phytochemical compounds that anti-bacterial function. Durian peel extract at concentration of 1% wt. inhibited the growth of Escherichia coli, Salmonella thyposa and Sthapylococcus aureus with a clear zone diameters of 7.4 mm, 8.2 mm and 8.6 mm, respectively. In anti-septic tests, hand sanitizer samples containing durian peel extract showed that the interaction between the concentration of durian peel extract and the sampling duration simultaneously gave a significant effect in reducing the number of microorganism colonies.